PENGARUH SUPLEMEN KALSIUM TERHADAP KADAR KALSIUM DARAH DAN BONE MINERAL DENSITY ( BMD ) PADA WANITA PENGGUNA KONTRASEPSI DEPO MEDROKSI PROGESTERON ASETAT ( DMPA ) - Robitah Asfur; M. Thamrin Tanjung; Mutiara Indah Sari (LP2MTBM MAKARIOZ, 2018)
Nowadays osteoporosis has became a global issue since the prevalence increased with lifestyle. Osteoporosis is a metabolic bone disease that can be seen by reduction in bone mass, than bone microarchitecture and the increment of bone fragility, so there will be a greater risk of fracture. Osteoporosis accurs with increasing aging population. One of the side effects of contraceptive depot medroksi progesterone acetate is osteoporosis, the use of contraceptive depot medroksi progesterone acetate which might inhibit the production of ovarian estradiol, theoretically increasing the risk of osteopenia and osteoporosis after menopause. Calcium is olso a mineral most often given to treat osteoporosis because of the effects of calcium on bone is directly related to bone formation. The research objective was to determine the effect of calcium supplementation on blood calcium levels and bone mineral dencity (BMD) in women on contraceptive depot medroksi progesterone acetate.This study is an experimental study with pre and post test design only with a simple randomization. Subjects were reproductive women around 21 years – 44 years old as many as 30 persons that were devided into 3 groups : normal group, osteopenia and osteoporosis. BMD and blood calcium of each group was examined and measured after given calcium supplement in 30 days, 60 to 90 days.The results showed that the given sample with calcium supplements for 30 days, 60 days and 90 days showed a significant increase in blood calcium levels and BMD ( p ≤ 0,05 ).